Preliminary results of Kansas State University dense plasma focus - Abdou, A. E; Ismail, M. I; Mohamed, A. E; Lee, S.; Saw, S. H.; Verma, R. (IEEE, 2012)
Kansas State University (KSU) dense plasma focus (DPF) is a 2.5-kJ DPF machine newly commissioned at the Plasma Radiation Physics Laboratory at KSU. The machine was designed to be used as a multiradiation source for applications in nuclear science and engineering. Neutrons are emitted from deuterium-deuterium (D-D) fusion reactions during high-power electric discharges at 17 kV, 140 kA, and 5 mbar. The machine circuit parameters were calculated using the short-circuit test. The emitted neutrons were measured using several radiation detection techniques. The 2.45-MeV characteristic D-D neutron energy was confirmed using the time-of-flight technique using a BC-418 plastic scintillator. The maximum neutron yield was roughly measured to be 2.8 × 108 neutrons per shot using a set of BTI BD-PND bubble detectors. Moreover, the neutron yield variation with pressure was measured and compared with the computed neutron yield using Lee model. Finally, the measured current showed good agreement with Lee six-phase model.